Association of Glycosylated Hemoglobin with Left Ventricular Diastolic Dysfunction in Type 2 Diabetes Mellitus - Darshan Rakhecha; Bharat Umakant Patil; Akshay Parakh; Samir Yelwatkar (Wolters Kluwer Medknow Publications, 2024)
Background: Diabetes is the leading cause of death and disability among cardiovascular disease patients. By 2025, India will have people with diabetes to one in every five diabetics worldwide. Aim: The study examines the relationship between glycosylated hemoglobin (HbA1c) levels and left ventricular diastolic dysfunction (LVDD) in type 2 diabetes patients. Settings and Design: This was a cross-sectional observational study. Materials and Methods: Over 2 years, 345 subjects with type 2 diabetes mellitus who gave informed consent and met the inclusion criteria were studied. The HbA1c test was performed using ion-exchange high-performance liquid chromatography. Electrocardiogram and two-dimensional echocardiography were used to evaluate cardiac dysfunctions. The relationship between potential variables and outcomes was determined using logistic regression. Statistical Analysis: All statistical analyses were carried out using STATA version 13 (College Station, TX: Stata Corp LP). Results: Mean HbA1c levels were found to be higher in patients with LVDD (10.40% ± 4.25%) compared to normal LVDD (7.51% ±3.18%) (P = 0.004) in the current study. The predicted left ventricular (LV) function with an area under the receiver operating characteristic curve of 0.883. Conclusions: LVDD is a common finding in people with type 2 diabetes. LVDD causes various cardiac complications, including LV hypertrophy, which is concerning. The current findings suggest that HbA1c is a reliable predictor of LVDD that can be used for screening in resource-limited areas where echocardiography is unavailable. In addition, regular HbA1c screening and blood sugar control can help prevent cardiovascular complications caused by LVDD in type 2 diabetic patients.